Sistem Pengontrol Temperatur dan Kelembaban Otomatis untuk Ruang Penyimpanan Buah - Zulkifli Amin; Muhamad Adha (Department of Mechanical Engineering, Universitas Andalas, 2017)
One of the preservation fresh fruit techniques is by using low temperature storage techniqe. This methode is intended to maintain good quality fresh fruits during the period of storage. Maintaining fresh friuts in the suggested low temperature and humidity lead to decelaration the activities of the causes of the spoilage of fresh fruits. Currently, fresh fruit storage methods is only focus on using low temperature storage methods regardless the prerequisites of the temperature nor humidity suggested best for fresh fruit preservation. Nowaday’s fruit storages used for maintaining fresh fruit longer is only operated by keeping the storage temperature constant on certain value during the period of storing and the value of the temperature is set manually. However, in order to optimise the results in fruit preservation, the temperature and humidity are also needed to be varied during priod of storage. This article illustrates the development of a system which can automatically control the temperature and humidity of the storage room in accordance with fruit preservation temperature and humidity suggested. In addition, , the temperature and humidity are also can be varied during priod of storage. This research is started by designing and building the electronic wiring system and controlling system. Next, continuing with programming for a microcontroller kit using Arduino IDE software. The container used for the fruit storage is a modified showcase fridge which is equipped with an ultrasonic humidifier and a DHT11 temperature and humidity sensor. The testing is carried out by observing the ability of the controlling unit apparatus to control the temperature and humidity of the storage container based on program inputed into the controller kit. The storage container is controlled to have temperature of 25°C, 10°C, and 25°C accordingly and the humidity of 85%. Both the temperature and humidity of the storage container are then measured and read manually using temperature and humiditymeter HTC-2. These temperature and humidity measurement data are compared with the temperature and humidity automatically measured by the sensors in the the control unit apparatus. The measurement results show that the values of temperatures and humidity measured by both methods are nearly the same. So, it can be concluded that the controlling unit apparatus is worked properly. It can control the temperature and humidity of the storage container as the program inputed into the controller kit and it can read the temperature and humidity accurately. In addition, the experiment using papaya fruits shows that the papaya fruits can be maintained fresh longer.